Author Correction: Predicting Alzheimer’s disease progression using multi-modal deep learning approach (Scientific Reports, (2019), 9, 1, (1952), 10.1038/s41598-018-37769-z) - Lee, Garam; Nho, Kwangsik; Kang, Byungkon; Sohn, Kyung Ah; Kim, Dokyoon; for Alzheimer’s Disease Neuroimaging Initiative (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 13 February 2019 This Article contains errors. A Supplementary Information file was omitted from the original version of this Article. The Supplementary Information file is now linked to this correction notice.